The relationship between COVID-19-specific health risk beliefs and the motivation to quit smoking: A UK-based survey. (1st October 2021) - Brown, Chris R.H.
Highlights: Perceived probability of COVID-19 infection predicted motivation to quit smoking. Perceived severity of COVID-19 infection did not predict motivation to quit smoking. Fear of COVID-19 indirectly predicted quit motivation through COVID-19 probability. The relationships were not accounted for by levels of other smoking health beliefs. Abstract: Background: In some individuals who smoke, the COVID-19 pandemic has triggered an increase in the motivation to quit smoking due to the potential higher risk of severe COVID-19 infection. However, this change is not universal, and the motivation to quit appears dependent upon factors such as fear of COVID-19 and perceived risk from COVID-19. In the current investigation both COVID-19 severity and infection probability beliefs were measured to isolate which beliefs correlated with the motivation to quit smoking. Methods: UK-based smokers ( N = 243) completed an online survey between September and October 2020, in which they reported their current motivation to quit smoking, fear of COVID-19, and their beliefs about how severe COVID-19 infection would be and how probable COVID-19 infection was. Results: The only significant predictor of the motivation to quit smoking was the perceived probability of COVID-19 infection, β = .22, p < .001, 95CI[.10, .34]. This relationship remained when controlling for the general perceived probability and severity of other smoking-related health risks, β = .20, p = .002, 95CI[.08, .32], suggesting a COVID-19-specific effect. Further, perceived probability of COVID-19 infection mediated the positive impact of fear of COVID-19 on motivation, β = .07, p = .006, 95CI[.03, .13]. Conclusions: The result places the perceived probability of COVID-19 infection as a central predictor of the motivation to quit during the pandemic. Based on this evidence, messaging aiming to facilitate smoking cessation during the pandemic should focus on the highly contagious nature of the virus to increase the motivation to quit.